Genagro - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Genagro is a Belgian NGO that promotes the coordination and development of scientific and technical initiatives designed to increase agricultural production. It takes a professional approach by working with tropical science soecialists,...